SOLVABILITY OF EQUATIONS INVOLVING PERTURBATIONS OF m-ACCRETIVE OPERATORS IN BANACH SPACES - Takeuchi, Y.; Toyoda, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
It is purpose of this paper to give several results for the solvability of the equation p ∈ Ax + Sx, where A is an m-accretive operator on a Banach space E and S is a mapping on a subset of E, with elementary proofs. We give proofs of them without using degree theory.